2012
DOI: 10.1257/jep.26.4.75
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Outcomes and Reforms in China

Abstract: Over the past few decades of economic reform, China's labor markets have been transformed to an increasingly market-driven system. China has two segregated economies: the rural and urban. Understanding the shifting nature of this divide is probably the key to understanding the most important labor market reform issues of the last decades and the decades ahead. From 1949, the Chinese economy allowed virtually no labor mobility between the rural and urban sectors. Rural-urban segregation was enforced by a househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
247
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(259 citation statements)
references
References 28 publications
2
247
1
9
Order By: Relevance
“…Rickne [22] studied the relationship between labor market conditions and social insurance participation among Chinese industrial firms and found that the increased scarcity of labor, large shares of uninsured workers, large shares of low-educated workers and those without labor unions were quantitatively important drivers of participation. The results of his tests were supported by the findings of the studies by different authors, namely: Cai [23], Meng [24], and Blechova et al [25] impact of aging population and rural-urban migration; Lu, Tao and Wang [26] unionization; Nyland et al [27]; Nielsen and Smith [28] negative association of firm size; Mao et al [29] positive association of firm size; Nyland et al [30], Cheng et al [31], Guo and Gao [32], Smyth et al [33] education impact; Nielsen et al [34], Smyth et al [33] urban residence permit; Gao et al [35] labor contract status.…”
Section: Literature Reviewsupporting
confidence: 67%
“…Rickne [22] studied the relationship between labor market conditions and social insurance participation among Chinese industrial firms and found that the increased scarcity of labor, large shares of uninsured workers, large shares of low-educated workers and those without labor unions were quantitatively important drivers of participation. The results of his tests were supported by the findings of the studies by different authors, namely: Cai [23], Meng [24], and Blechova et al [25] impact of aging population and rural-urban migration; Lu, Tao and Wang [26] unionization; Nyland et al [27]; Nielsen and Smith [28] negative association of firm size; Mao et al [29] positive association of firm size; Nyland et al [30], Cheng et al [31], Guo and Gao [32], Smyth et al [33] education impact; Nielsen et al [34], Smyth et al [33] urban residence permit; Gao et al [35] labor contract status.…”
Section: Literature Reviewsupporting
confidence: 67%
“…Tuition is free for the 9 years of schooling (primary and lower-middle school education), although students normally have to pay costs associated with purchasing books and tools, transportation, fees related to extracurricular activities, and fees for boarding school (which is quite common in rural areas). 29 In addition, there are opportunity costs in terms of forgone earnings (especially from employment opportunities in cities), which may be increasingly high as children enter their late teens (Meng, 2012).…”
Section: Human Capital Investment In Childrenmentioning
confidence: 99%
“…In urban China, migrants from the rural areas have limited access to the social services to which urban hukou holders are entitled. 16 For example, in 2010, 20 percent of the migrants had access to health insurance, as opposed to 87 percent of workers with urban hukou (Meng 2012); migrant children are often denied access to public schools; and so on. As a result of institutional discrimination, "[t]he labor markets for urban hukou workers and migrant workers are segregated" (Meng 2012, p. 92, emphasis added).…”
Section: Resultsmentioning
confidence: 99%
“…This regime and the policy stance forging it are tantamount to institutional non-integration (social non-integration) which, as we have argued, curbs an incentive to assimilate in the economic sphere and increase productivity. There is concomitant evidence of an earnings gap: hourly wages of urban hukou workers are double those of migrants (Meng 2012). This segregation, reinforced by the hukou policy, could be why migrants do not feel the heat of this gap.…”
Section: Resultsmentioning
confidence: 99%